HUKUM ADAT PEMINANGAN DAN PERKAWINAN DI KOMUNITAS MUSLIM MINORITAS JIMBARAN BALI - Rahman, Fathur (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
To find out how far the role of customary law on the pattern of life in thisengagementl and marriage in the village of Jimbaran, then this article isspecifically limited to the aspects of the engagement and marriage, whichis a global problem that was described in a Compilation of Islamic Law(KHI). According to article 11 and 12 KHI proposal can be directly performed by a desire to find a mate pair, but can also be done by atrusted intermediary, a proposal can be made to a woman who is still avirgin or the widow who had completed their term appointed time, aswell as for getting marriage catch at least 19 years of age and fianceeat least 16 years of age. Whereas according to Jimbaran customary law,the mature is a requirement for getting sustainability engagement andmarriage, does sustainability in this case is the 23-year-old girl whilea man aged 27 years and also has experienced sustained at least havea job and never traveled out of the province Bali.